The Relationship between Self-Regulation Learning and Student Learning Motivation - M. Ramadan; Rici Kardi; Mori Rianto (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe students’ self-regulated learning, their learning motivation, and to examine the relationship between self-regulated learning and learning motivation among students at SMP Muhammadiyah 6 Padang. The research employed a quantitative method with a correlational approach. The population consisted of 98 students, all of whom were selected using a total sampling technique. The research instrument was a questionnaire that had been tested for validity and reliability. The findings revealed that students’ self-regulated learning fell into the low category, while their learning motivation was in the moderately high category. Correlation analysis indicated a weak relationship between self-regulated learning and learning motivation. The implications of this study recommend that school counselors provide services to enhance students’ self-regulation and learning motivation.